The Association Between Coping Strategies, Resilience, and Flourishing Among Students at Large U.S. University During the COVID-19 Pandemic: A Mixed Methods Research Study - Chatfield, Sheryl L.; Bista, Saroj; DeBois, Kristen A.; Kenne, Deric R. (Building Healthy Academic Communities Journal, 2022)
Background: Mental illness indicators increased among U.S. university students in recent years; COVID-19 associated disruptions presented additional mental health challenges for students. Aim: This research aimed to assess the relationship between coping strategies identified by university students and scores on resilience and flourishing scales and to identify additional themes that described student experiences during the COVID-19 pandemic. Methods: An online survey was administered to students at a large public Midwestern University. Quantitative data were assessed using nonparametric tests for association and qualitative data were analyzed using cycles of open coding. Results: Most of the 3,473 respondents were female (76.5%) and white (83.6%), with a mean age of 24.67 years (SD = 8.08). The most frequent coping strategy was physical activity participation (n = 712), followed by socializing (n = 507). The highest resilience and flourishing scores were associated with compliance to COVID-19 associated recommendations or spiritual activities. Qualitative themes included the value of focusing on controllable aspects, the need to be strong for others, and the experience of academic overload during transition to online learning. Conclusions: Universities should endeavor to provide ongoing availability of counseling during university disruptions. Universities might also consider proactive efforts to guide students toward proficiency in strategies that improve coping skills, including some that do not center around technology.